Brine elimination by hybridization of a novel brine-recycle bubble-column humidification-dehumidification system with a multiple-effect distillation system. (1st August 2020) - Ghofrani, Iraj; Moosavi, Ali
Highlights: A new cost-effective hybrid system with zero liquid discharge approach is proposed. A novel brine-recycle humidification-dehumidification system is introduced. Up to 10 percent cost saving is achieved by hybridization. The fresh water environmental impact is reduced by 12% with hybridization. 32.8% environmental impact reduction is achieved by the 22.8% increase in water cost. Abstract: Over the past decades, drastic growth in the installed capacity of seawater desalination systems has increased the energy consumption and brine discharge to the environment. However, using renewable energies and zero liquid discharge systems for minimizing these challenges is limited due to the higher fresh water cost of the systems rather than that of the conventional systems. In this research, a bubble-column humidification-dehumidification zero liquid discharge system is coupled with a multiple-effect distillation/vapor compression system in a novel way to overcome the high water cost of conventional zero liquid discharge systems. Further, the base system and the solar-powered system is examined in exergy, exergoeconomic, and exergoenvironmental viewpoints. For the analyses, 4–8 effects are considered for the multiple-effect distillation system, and 1–3 stages are considered for the brine-recycle humidification-dehumidification system. Hybridization of the brine-recycle humidification-dehumidification system can reduce the water cost up to 10% compared to the non-hybrid system, and can reduce the fresh water environmental impact from 2.59 Pts/m 3 to 2.28 Pts/m 3 . The effects of coupling the hybrid system with a solar farm on the cost and environmental impact are also investigated based on the winter, spring, summer, and autumn design conditions. Based on the results, coupling a multiple-effect distillation system with a multistage brine-recycle humidification-dehumidification desalination system can effectively eliminate the negative desalination environmental impacts in a cost-effective way.